Measurement of the CP-violating asymmetries in B(0)-> K(s)(0)pi(0) and of the branching fraction B(0)-> K(0)pi(0) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2008)
We present a measurement of the time-dependent CP-violating asymmetries in B0→KS0π0 decays based on 383×106 Υ(4S)→BB̄ events collected by the BABAR experiment at the PEP-II asymmetric-energy B Factory at the Stanford Linear Accelerator Center. We measure the direct CP-violating asymmetry CKS0π0=0.24±0.15±0.03 and the CP-violating asymmetry in the interference between mixing and decay SKS0π0=0.40±0. 23±0.03, where the first errors are statistical and the second are systematic. On the same sample, we measure the decay branching fraction, obtaining B(B0→K0π0)=(10.3±0.7±0.6)×10-6. © 2008 The American Physical Society.